2019
DOI: 10.1111/rec.13029
|View full text |Cite
|
Sign up to set email alerts
|

In‐stream habitat and macroinvertebrate responses to riparian corridor length in rangeland streams

Abstract: Conservation and restoration of riparian vegetation in agricultural landscapes has had mixed success at protecting in-stream habitat, potentially due to the mismatch between watershed-scale impacts and reach-scale restoration. Prioritizing contiguous placement of small-scale restoration interventions may effectively create larger-scale restoration projects and improve ecological outcomes. We performed a multi-site field study to evaluate whether greater linear length of narrow riparian tree corridors resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…Developing woody vegetation (large trees) in a 10 m buffer directly adjacent to the river bank is most effective and already provides most of the effect of wider buffers. These results indicate that buffer width is less important compared to length, and woody buffers should be as long as possible to prevent the continuous heating in unshaded reaches, similar to the conclusions drawn by Stanford et al (2020). However, wider buffers up to 30 m are known to increase other functions like nutrient retention (Gericke et al, 2020; Sweeney & Newbold, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Developing woody vegetation (large trees) in a 10 m buffer directly adjacent to the river bank is most effective and already provides most of the effect of wider buffers. These results indicate that buffer width is less important compared to length, and woody buffers should be as long as possible to prevent the continuous heating in unshaded reaches, similar to the conclusions drawn by Stanford et al (2020). However, wider buffers up to 30 m are known to increase other functions like nutrient retention (Gericke et al, 2020; Sweeney & Newbold, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Similarly, Stanford et al. (2019) found that only 1 km of riparian tree corridor could counteract 1.5°C water temperature warming in intermittent Mediterranean streams. In mid‐order channels in our study area (Turunen et al., 2019), the riparian forest did not affect stream water temperature, probably because of wider channels (less shading effect in forested reaches) and larger water volume causing higher thermal inertia (Quinn & Wright‐Stow, 2008; Ryan et al., 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies reported more silted stream beds in stream reaches that drain within agricultural fields compared to reaches that maintain riparian forests (e.g. Jones et al., 1999; Sponseller et al., 2001; Stanford et al., 2019). In comparison, mid‐order agricultural streams in the same area exhibited no physical stream habitat condition differences among forested and open reaches (Turunen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations